Cellular mRNA recruits the ribosome via eIF3-PABP bridge to initiate internal translation. Issue 5 (4th May 2017) - Thakor, Nehal; Smith, M. Duane; Roberts, Luc; Faye, Mame Daro; Patel, Harshil; Wieden, Hans-Joachim; Cate, Jamie H. D.; Holcik, Martin
ABSTRACT: IRES-mediated translation of key cell fate regulating genes has been implicated in tumorigenesis. Concerted action of canonical eukaryotic initiation factors and IRES transacting factors (ITAFs) was shown to regulate cellular IRES mediated translation; however, the precise molecular mechanism of ribosome recruitment to cellular IRESes remains unclear. Here we show that the X-linked inhibitor of apoptosis (XIAP) IRES operates in an evolutionary conserved viral like mode and the structural integrity, particularly in the vicinity of AUG, is critical for ribosome recruitment. The binding of eIF3 together with PABP potentiates ribosome recruitment to the IRES. Our data support the model in which eIF3 binds directly to the XIAP IRES RNA in a structure-dependent manner and acts as a scaffold for IRES RNA, PABP and the 40S ribosome.